PENGARUH PERCEIVED CONTENT ENTERTAINMENT, PERCEIVED PRODUCT INFORMATIVENESS, DAN PERCEIVED SOURCE CREDIBILITY DALAM KONTEN TIKTOK AFFILIATE TERHADAP MINAT BELI DI SOCIAL COMMERCE TIKTOK SHOP - Permata Ayuning Mulia, Catharina; Surayya Ulfa, Nurist (Interaksi Online, 2024)
Affiliate marketing on TikTok has the potential to be an effective strategy for increasing consumer purchase intention. Products or brands can achieve broad promotion by involving third parties such as content creators through TikTok Affiliate programs. Despite numerous successes, not all affiliates manage to enhance purchase intention effectively. This study aims to investigate the impact of perceived content entertainment, perceived product informativeness, and perceived source credibility in TikTok Affiliate content on purchase intention in social commerce via TikTok Shop. The theoretical framework employed is the Theory of Reasoned Action (TRA). The research involves 100 respondents who meet the criteria of being male and female, aged 18-25 years, and active TikTok users. Hypothesis testing using F-tests in multiple linear regression indicates a positive influence of perceived content entertainment, perceived product informativeness, and perceived source credibility in TikTok Affiliate content on purchase intention in social commerce via TikTok Shop, with significance levels at 0.000 < 0.05. This study highlights the importance of information, entertainment, and credibility in affiliate content to enhance purchase intention in social commerce on TikTok Shop.